Nosocomial BK Polyomavirus Infection Causing Hemorrhagic Cystitis Among Patients With Hematological Malignancies After Hematopoietic Stem Cell Transplantation. Issue 9 (21st April 2017) - Kato, J.; Mori, T.; Suzuki, T.; Ito, M.; Li, T. C.; Sakurai, M.; Yamane, Y.; Yamazaki, R.; Koda, Y.; Toyama, T.; Hasegawa, N.; Okamoto, S.
Abstract : BK polyomavirus (BKPyV) is recognized as a pathogen that causes diseases such as hemorrhagic cystitis and nephritis after allogeneic hematopoietic stem cell transplantation (HSCT) or renal transplantation. BKPyV‐associated disease is thought to occur through reactivation under immunosuppression. However, the possibility of its nosocomial transmission and the clinical significance of such transmission have not been elucidated. During a 6‐month period, nine adult patients (median age: 47 years) who had hematological disorders and who were treated with HSCT (n = 7) or chemotherapy (n = 2) in a single hematology department developed hemorrhagic cystitis due to BKPyV infection. The polymerase chain reaction products of BKPyV DNA obtained from each patient were sequenced. Of the nine patients, six had subtype I, 2 had subtype IV, and 1 had subtype II or III. In the alignment of sequences, four and two of the six subtype I strains were completely homologous (100%). These results strongly suggest that BKPyV has the potential to cause nosocomial infection within a medical facility, especially among recipients of HSCT. Further studies are clearly warranted to elucidate the route(s) of BKPyV transmission in order to establish optimal infection control. Abstract : This study suggests that BK polyomavirus has the potential to cause nosocomial infection in a medical facility, especially in hematopoietic stem cell transplant recipients.